Microalbuminuria in children and adolescent with type 1 Diabetes mellitus attending the diabetic center of children welfare teaching hospital. - Alzubaidi, Munib A.; jawad, Ali A. (Journal of the Faculty of Medicine Baghdad, 2014)
Backgrounds: Despite advances in management of diabetes mellitus, it remains one of the major causes of morbidity and mortality, yet diabetic nephropathy is one of the main complications of diabetes mellitus. .Microalbuminuria is the beginning to the renal complications of diabetes mellitus; it is a significant index of early detection as well as monitoring the progression of diabetic nephropathy.                                                                                                                                        Aim of the study: to estimate the presence of microalbuminuria as predictor for nephropathy among children and adolescent with type1 diabetes mellitus and to study the effect of various factors on incidence of microalbuminuria in these patients.                                                                                                                Subjects and methods: this study was carried out in the Children Welfare Teaching Hospital/ Medical City over ten months period. Fifty patients with type 1 diabetes and fifty non-diabetic children matched for age and sex were included in the study as control group. History was taken, physical examination and investigations done for all subjects. Early urine samples were used to estimate albumin/creatinine ratio to detect microalbuminuria. Statistical analysis done using T test and chi square, P value < 0.05 regarded as statistically significant.                                                                            Results: out of 50 patients with type 1 diabetes, 35 (70%) had microalbuminuria. There was significant association between presence of microalbuminuria and increasing age (P value 0.04), increasing duration of diabetes (P value 0.03) and glycemic control level(P value =0.04).Seven (46.6% ) patients with duration of